A HEALTH WORKERS’ PERSPECTIVE ON TB PREVENTIVE THERAPY FOR CONTACTS OF TB PATIENTS: A CROSS-SECTIONAL STUDY FROM SOUTH WESTERN UGANDA - Mugisha, Dan; Owino Odongo, Alfred; Mbaruk, Suleiman (Student's Journal of Health Research Africa, 2024)
Background Tuberculosis Preventive Therapy is the key, cost-effective Tuberculosis (TB) prevention strategy but its coverage remains sub-optimal, globally. The objective of the study was to establish factors associated with TPT prescription among PBC TB patients. Methods A cross-sectional study was conducted. Data was collected using a data abstraction tool and a self-administered, semi-structured questionnaire from the 17 TB diagnostic and treatment health facilities in Bushenyi district, South Western Uganda. Abstract data was analyzed in Excel for descriptive statistics. Factor analysis was done on the data collected using the questionnaire using. R Core Team, 2023 was used for the analysis. Results Of the 781 contacts line-listed for contact tracing, only 442 (77.1%) were prescribed TPT, which is below the 90% target. Factor analysis revealed six factors affecting TPT prescription and these are Latent TB testing, TPT service delivery, TPT financing, human resources for TPT, Monitoring, and evaluation for TPT, and health workers' attitude towards TPT. In the bivariate logistic regression analysis, perception of patient as being uncomfortable with TPT (OR 4.42 95% CI:1.87-11.7; p=0.001), low healthcare worker’s knowledge of TB and TPT (OR 3.94 95% CI: 1.61-11.1; p=0.005), and negative healthcare worker’s attitude towards TPT prescription (OR 4.56 95% CI: 1.28-29.2; p = 0.045) were significantly associated with low TB prescription. In multivariate logistic regression, the perception of the patient is uncomfortable with TPT (aOR 5.58 95% CI: 2.18-16.0; p = <0.001). Gaps in knowledge among healthcare workers about TB and TPT (aOR 5.97 95% CI: 2.08-19.6; p=0.002) were significantly associated with less likelihood of TPT prescription by a healthcare worker. Conclusions Whereas TPT is an efficient intervention for the prevention of TB, health system factors remain impediments to its implementation. Recommendation Studies be conducted to evaluate the impact of TPT on reducing TB incidence among contacts of PBC TB patients.